Endoscopic vs Open Decompression of the Ulnar Nerve in Cubital Tunnel Syndrome: A Prospective Randomized Double-Blind Study. Issue 6 (21st August 2015) - Schmidt, Sarah; Kleist Welch-Guerra, Waltraud; Matthes, Marc; Baldauf, Jörg; Schminke, Ulf; Schroeder, Henry W.S.
Abstract: BACKGROUND: Prospective randomized data for comparison of endoscopic and open decompression methods are lacking. OBJECTIVE: To compare the long- and short-term results of endoscopic and open decompression in cubital tunnel syndrome. METHODS: In a prospective randomized double-blind study, 54 patients underwent ulnar nerve decompression for 56 cubital tunnel syndromes from October 2008 to April 2011. All patients presented with typical clinical and neurophysiological findings and underwent preoperative nerve ultrasonography. They were randomized for either endoscopic (n = 29) or open (n = 27) surgery. Both patients and the physician performing the follow-up examinations were blinded. The follow-up took place 3, 6, 12, and 24 months postoperatively. The severity of symptoms was measured by McGowan and Dellon Score, and the clinical outcome by modified Bishop Score. Additionally, the neurophysiological data were evaluated. RESULTS: No differences were found regarding clinical or neurophysiological outcome in both early and late follow-up between both groups. Hematomas were more frequent after endoscopic decompression ( P = .05). The most frequent constrictions were found at the flexor carpi ulnaris (FCU) arch and the retrocondylar retinaculum. We found no compressing structures more than 4 cm distal from the sulcus in the endoscopic group. The outcome was classified as "good" or "excellent" in 46 out of 56 patients (82.1%). Eight patients did not improve sufficiently or had a relapse and underwent a second surgery. CONCLUSION: The endoscopic technique showed no additional benefits to open surgery. We could not detect relevant compressions distal to the FCU arch. Therefore, an extensive far distal endoscopic decompression is not routinely required. The open decompression remains the procedure of choice at our institution.